The Impact of Video-Based Education through the SAKTI Remaja Application on Adolescents' Knowledge, Attitudes, and Mental Health Conditions - Reni Nurhidayah; Dhita Kurnia Sari; Prima Dewi Kusumawati; Ardi Bastian (Journal Of Nursing Practice, 2025)
Background: Adolescence is a transitional period marked by rapid physical, cognitive, emotional, and social changes. Inability to manage these changes can lead to stress and negatively affect mental health, including anxiety, depression, and destructive behaviors. In Indonesia, the prevalence of mental health problems among adolescents continues to rise, particularly in Islamic boarding schools (pesantren), where psychological well-being is often overlooked. Objective: This study aimed to evaluate the effectiveness of video-based mental health education through the SAKTI Remaja mobile application in improving adolescents’ knowledge, attitudes, and mental health conditions in Islamic boarding schools. Methods: A quasi-experimental design with pre-test and post-test was used. A total of 80 students from a pesantren in Baron District, Nganjuk Regency, were selected using purposive sampling. The intervention was conducted over two weeks using the SAKTI Remaja app, which provided educational videos on emotional regulation, stress management, stigma, and help-seeking behavior. Instruments included the Adolescent Mental Health Literacy Questionnaire (AMHLQ), Mental Health Attitude Scale (MHAS), and Self-Reported Mental Health Condition Checklist. Data were analyzed using paired t-tests and Wilcoxon signed-rank tests with a significance level of p < 0.05. Results: There was a significant improvement in knowledge (pre-test = 56.5; post-test = 82.5; p < 0.001), mental health attitudes (pre-test = 62.3; post-test = 75.2; p < 0.001), and a decrease in mental health symptoms (pre-test = 3.5; post-test = 2.1; p < 0.001). These findings indicate that video-based education through the SAKTI Remaja app effectively enhanced mental health literacy, promoted positive attitudes, and reduced psychological symptoms among adolescents in pesantren. Conclusion: The SAKTI Remaja application is an innovative and effective educational intervention for improving knowledge, attitudes, and mental health conditions among adolescents in Islamic boarding schools. This video-based education model offers a relevant promotive and preventive strategy that can be integrated into youth health programs in religious-based educational institutions.